PENINGKATAN HASIL BELAJAR BIOLOGI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION - Mas’ud, Asrianty (Jurnal BIOEDUIN, 2018)
Investigation group is a type of cooperative learning which stresses on the participation, activeness, and involves students in planning, determining the topic as well as the way to investigate. An investigation group learing type also guides students to think independently. The study aims was increasing students’ learning outcome in Biology with group investigation learning model. This study is a classroom action research conducted in two cycles. The result of the study reveal that students’ learning in Biology improves 58.62% from cycle I to cycle II for students’ learning completeness. Keywords: group investigation, learning outcome, cooperative leraning